Aberrant neuronal expression of mitotic protein, tau and Bax in the rat brain after injection of Abeta(25-35) into the amygdala - Hong, Dao-Jun; Pei, Ai-Lin; Sun, Feng-Yan; Zhu, Cui-Qing (Sheng li hsüeh pao, 2003)
Recent evidence indicates that the aberrant neuronal expression of mitotic proteins in Alzheimer's disease (AD) brain may be related to AD pathological changes. To investigate whether the toxicity of beta-amyloid protein (Abeta) induces mitotic proteins expression in adult rat brain, we used immunohistochemical and integral optical density analytic method to analyze the adult rat brains, which had been injected with Abeta(25-35) into unilateral amygdala. Results showed that the levels of neurofibrillary tangle (NFT) related phosphorylated tau protein and apoptosis related protein Bax were increased in Abeta(25-35) injected rat brains, meanwhile the aberrantly expression of mitotic protein cyclin A and cyclin B1 was also detected at 7 d after operation, but the level of cyclin A decreased and cyclin B1 disappeared at 21 d. Immunofluorescence double labeling presented that cyclin B1 was partially co-localized with Bax or phosphorylated tau protein, whereas Bax and phosphorylated tau protein seldom co-localized.